Control of the geomorphology and gas hydrate extent on widespread gas emissions offshore Romania - Riboulot Vincent; Cattaneo Antonio; Scalabrin Carla; Gaillot Arnaud; Jouet Gwénaël; Ballas Grégory; Marsset Tania; Garziglia Sébastien; Ker Stephan (Bulletin de la Société géologique de France, 2017)
The Romanian sector of the Black Sea deserves attention because the Danube deep-sea fan is one of the largest sediment depositional systems worldwide and is considered the world's most isolated sea, the largest anoxic water body on the planet and a unique energy-rich sea. Due to the high sediment accumulation rate, presence of organic matter and anoxic conditions, the Black sea sediments offshore the Danube delta is rich in gas and thus shows Bottom Simulating Reflectors (BSR). The cartography of the BSR over the last 20 years, exhibits its widespread occurrence, indicative of extensive development of hydrate accumulations and a huge gas hydrate potential. By combining old and new datasets acquired in 2015 during the GHASS expedition, we performed a geomorphological analysis of the continental slope north-east of the Danube canyon compared with the spatial distribution of gas seeps in the water column and the predicted extent of the gas hydrate stability zone. This analysis provides new evidence of the role of geomorphological setting and gas hydrate extent in controlling the location of the observed gas expulsions and gas flares in the water column. Gas flares are today considered an important source of the carbon budget of the oceans and, potentially, of the atmosphere.